2006
DOI: 10.1186/bf03351994
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and spectral characteristics of L-band and VHF scintillations and their impact on trans-ionospheric communications

Abstract: Amplitude scintillations recorded at 1.5 GHz frequency during the high (1998)(1999) and low (2004)(2005) sunspot activity periods over a low latitude station, Waltair (17.7 • N, 83.3• E) revealed that the L-band scintillations mostly occur during the post-sunset to midnight hours peaking around 21:00 hr local time with maximum occurrence during equinoxes, moderate during winter and minimum during the summer months. The occurrence, as well as the intensity of scintillations, is found to be strongly dependant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Also, the occurrence of scintillations is modulated by the seasonal effect, with maximum occurrences during the equinox months followed by winter and a minimum occurrence during summer months. During the moderate to high sunspot activity periods, the seasonal modulation in the occurrence pattern of scintillations is significant (DasGupta et al, 1983;Rama Rao et al, 2006). However, during relatively low sunspot number periods, such as [2004][2005], and during the descending phase of the sunspot number, the seasonal control on the scintillation activity is predominantly perceptible over the sunspot number dependence, as may be seen from Fig.…”
Section: L-band Scintillations In the Indian Regionmentioning
confidence: 80%
“…Also, the occurrence of scintillations is modulated by the seasonal effect, with maximum occurrences during the equinox months followed by winter and a minimum occurrence during summer months. During the moderate to high sunspot activity periods, the seasonal modulation in the occurrence pattern of scintillations is significant (DasGupta et al, 1983;Rama Rao et al, 2006). However, during relatively low sunspot number periods, such as [2004][2005], and during the descending phase of the sunspot number, the seasonal control on the scintillation activity is predominantly perceptible over the sunspot number dependence, as may be seen from Fig.…”
Section: L-band Scintillations In the Indian Regionmentioning
confidence: 80%
“…Steep power spectral slope as high as ∼ 5-6 for early evening scintillation at 257 MHz frequency near equatorial region of solar maximum period is reported by Basu et al (1983), and in the range of 2.5-5.6 from equatorial anomaly region by Iyer et al (2006). The high (low) values of spectral indices in the pre-midnight (post-midnight) hours may be attributed to a thick layer (comparatively thinner) of irregularities, common during equinoctial months of the solar maximum epoch (Rama Rao et al, 2006). In the developing phase, although irregularities of various scale sizes may generate simultaneously, lower scale size irregularities decay first.…”
Section: Spectral Features Of Scintillation Variabilitymentioning
confidence: 99%
“…3) are showing moderate fade rates that vary between ~7 and ~23 fad min -1 (~0.11 and 0.38 cycles s -1 ), and the fading rates of scintillations recorded on 22 March 2013 (Fig. 4) As the moderate intensity and relatively fast fading rates of VHF scintillations are due to multiple scattered radio waves with a wide range of irregularities embedded in plasma bubbles, which are moving across the FLEETSAT satellite propagation path, the observed scintillations in the present study would have originated from a wide range of irregularities that were initiated initially over the equatorial station (Iyer et al 2006;Rama Rao et al 2006;Basu et al 2009;Prasad et al 2012). …”
Section: Power Spectral Characteristics Of Scintillationsmentioning
confidence: 56%
“…The severe scintillations, for which the scintillation index is usually greater than 0.45, which is ≈10 dB, are able to interrupt the GPS receiver operation by causing in-phase and quadrature signal fading, which makes the proper phase determination using a tracking loop nearly impossible. Further, it was reported that a typical GPS receiver loses its lock for a short duration from 1 -4 min during severe scintillation events, thereby affecting even the integrity of satellite based augmentation systems (SBAS) (Rama Rao et al 2006).…”
Section: Introductionmentioning
confidence: 99%